Solar particle event storm shelter requirements for missions beyond low Earth orbit. (May 2018) - Townsend, L.W.; Adams, J.H.; Blattnig, S.R.; Clowdsley, M.S.; Fry, D.J.; Jun, I.; McLeod, C.D.; Minow, J.I.; Moore, D.F.; Norbury, J.W.; Norman, R.B.; Reames, D.V.; et al.
ABSTRACT: Protecting spacecraft crews from energetic space radiations that pose both chronic and acute health risks is a critical issue for future missions beyond low Earth orbit (LEO). Chronic health risks are possible from both galactic cosmic ray and solar energetic particle event (SPE) exposures. However, SPE exposures also can pose significant short term risks including, if dose levels are high enough, acute radiation syndrome effects that can be mission- or life-threatening. In order to address the reduction of short term risks to spaceflight crews from SPEs, we have developed recommendations to NASA for a design-standard SPE to be used as the basis for evaluating the adequacy of proposed radiation shelters for cislunar missions beyond LEO. Four SPE protection requirements for habitats are proposed: (1) a blood-forming-organ limit of 250 mGy-equivalent for the design SPE; (2) a design reference SPE environment equivalent to the sum of the proton spectra during the October 1989 event series; (3) any necessary assembly of the protection system must be completed within 30 min of event onset; and (4) space protection systems must be designed to ensure that astronaut radiation exposures follow the ALARA (As Low As Reasonably Achievable) principle.